Effect of modification on the physicochemical and thermal properties of organophilic clay modified with Octadecylamine - Olalekan, Salawudeen Taofeeq; Qudseih, Isam Yassin; Kabbashi, Nassereldeen Ahmed; Al-Khatib, Ma'an Fahmi Rashid; Muyibi, Suleyman Aremu; Yusof, Faridah; Shah, Qasim Hussain (IJENS Publishers, 2010)
Organophilic clay was modified by ion exchange reactions using Octadecylamine. The reaction process was carried out at a temperature of 70oC for 90 minutes reaction time in a batch reactor equipped with a mechanical stirrer rotating at a speed of 300 rpm. Physicochemical and thermal properties of the clay before and after modification were determined and compared using Field Emission Scanning Electron Microscope/ Energy Dispersive X-ray spectroscopy (FESEM/EDX),Fourier transform infrared spectroscopy (FT-IR) and Thermogravimetric Analyzer (TGA). FESEM images show clearly the micro structural differences between the modified and unmodified clay while EDX shows a compositional changes between modified and unmodified clay with the presence of 7.27% carbon in the modified clay. The analysis of FT-IR spectra shows the attachment of some functional groups which are mostly alkyl and hallo-alkyl groups. This is an indication of proper modification. TGA plots of both pure unmodified and organically modified clay attained stability at a temperature between 500oC and 900oC after reduction in weight due to evaporation of moisture and decomposition of the adhered Alkylammonium salts between 30oC and 500oC. This confirmed that thermal stability of the organically modified clay compared favorably with pure natural clay under TGA.